Variable Outcome of Viral Hepatitis Among Diabetes Patients and its High Prevalence - Muhammad Naeem Aslam, Ghulam Hassan, Sohail Hussain, Agha Wali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to assess the clinical and biochemical features of people with diabetes and acute viral hepatitis. Study Design: Prospective/Observational study Place and Duration: Conducted at Department of Gastroenterology Mayo Hospital Lahore, during from the period July 2021 to June 2022. Methods: Ninety-two diabetics participate in this study. The ages of the participants in the study covered the gamut from 24 to 70. Body mass index (BMI), place of residence, and level of education were collected after patients gave their informed consent. Comorbidities among all cases were assessed. Patients' vital signs and metabolic profiles were tracked continuously during their hospital stay. The analysis was done in SPSS 20.0. Results: The current study found that men were higher than women (p .009). Hepatitis E was by far the most common, followed by hepatitis B and A. We found decreased ALT 841.9±51.11 U/L and albumin levels 912.18±22.42 mg/dl, the average blood bilirubin levels of people with diabetes were significantly higher 20.117±9.251 mg/dl. 52 (56.5%) patients had smoking history. HTN, CLD and IHD was the most common comorbidities among all cases. The average length of time spent in the hospital was 25.8±5.61days. Frequency of died patients was 6 (6.5%). Conclusion: Among patients with diabetes and AVH, we discovered that ALT was lower, bilirubin was greater, the risk of liver failure was higher, and the length of hospital stay was longer. However, this mortality rate was 6.5% in diabetes patients. Keywords: Mortality, Clinical Outcomes, Acute Viral Hepatitis, Diabetes